Duty, Discipline, and Dreams: Childhood and Time in Hindutva Nation - Thapliyal, Nisha (Journal of Childhood Studies, 2023)
Childhood and time constitute key sites of regulation for nationalist authoritarian regimes. However, the influence of time on contemporary nationalist discourses of childhood located in the Global South remains an underresearched area. This paper critically analyzes two spectacles involving Hindu nationalist Indian Prime Minister Narendra Modi and secondary school students on the occasions of Teachers Day 2014 and 2015. Temporal language, markers, and symbols rooted in discourses of colonialism/Orientalism, Brahminical Hinduism, and capitalist development are deconstructed to show how nationalist constructions of childhood can penetrate deep into the everyday lives of particular children who are deemed worthy to serve their nation. The paper concludes by highlighting specific ways in which time and temporality are weaponized to reproduce and legitimize a social hierarchy of childhoods that is necessary to sustain Hindu ethno-religious nationalism.